1998
DOI: 10.1017/s0022029998003124
|View full text |Cite
|
Sign up to set email alerts
|

Productive and reproductive performance in cattle infected with bovine leukosis virus

Abstract: Economic losses caused by enzootic bovine leukosis (EBL) have been of interest since World War II, when the neoplastic form of EBL increased dramatically in Europe. Olson (1974) and House et al. (1975) showed that animals with lymphosarcoma caused by the bovine leukosis virus (BLV) had reduced milk yields, a less efficient reproductive performance and high veterinary costs and mortality rates, while many carcasses were rejected at slaughter. However, the actual impact of BLV infection in cattle without lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…Studies in the United States (Ott et al, 2003) and Canada (Sargeant et al, 1997) have demonstrated a negative effect of BLV infection on milk production at the herd level. Similarly, Olson (1974), Da et al (1993), andD'Angelino et al (1998) showed that animals with persistent lymphocytosis and lymphosarcoma caused by BLV infection had reduced milk yields. However, no association has been found between BLV infection and milk production in several studies in individual animals (Jacobs et al, 1991;Kale et al, 2007;Tiwari et al, 2007).…”
Section: Introductionmentioning
confidence: 92%
“…Studies in the United States (Ott et al, 2003) and Canada (Sargeant et al, 1997) have demonstrated a negative effect of BLV infection on milk production at the herd level. Similarly, Olson (1974), Da et al (1993), andD'Angelino et al (1998) showed that animals with persistent lymphocytosis and lymphosarcoma caused by BLV infection had reduced milk yields. However, no association has been found between BLV infection and milk production in several studies in individual animals (Jacobs et al, 1991;Kale et al, 2007;Tiwari et al, 2007).…”
Section: Introductionmentioning
confidence: 92%
“…Garcia et al 7 e Birgel Jr. et al 8 não encontraram interferência na imunidade humoral e celular, enquanto Azedo et al 9 identificaram alterações funcionais em fagócitos mononucleares de animais sororreagentes. D'Angelino et al 10 ressaltaram a possibilidade de quedas na produção leiteira em animais sororreagentes, porém não foram observadas diferenças nos índices reprodutivos. Em rebanhos leiteiros dos Estados Unidos, foi estimada queda de 3% na produção, significando perda de US$ 59 por fêmea nos rebanhos sororreagentes 11 .…”
Section: Introductionunclassified
“…At any age animals can be infected with bovine leukaemia virus (BLV), but tumour (lymphosarcomas) is seen typically in the animals over 3 years old. Infections are usually sub clinical; only 30-70% of the infected cattle develop the persistent lymphocytes and only 0.1-10% -develop the tumours [3].…”
Section: Introductionmentioning
confidence: 99%